Traditional Chinese medicine in the prevention of diabetes mellitus and cardiovascular complications: mechanisms and therapeutic approaches - Chen, Caixia; Gao, Hui; Wei, Ying; Wang, Yaxi (Frontiers in Pharmacology, 2025)
Diabetes mellitus (DM) is a chronic endocrine and metabolic disorder characterized by persistent hyperglycemia that poses serious threats to human health and quality of life. The morbidity, disability, and mortality rates of cardiovascular complications stemming from chronic hyperglycemia are primary factors affecting the lifespan of patients with diabetes. Currently, there is no cure for DM. Standard biomedical treatments mostly control the symptoms using insulin injections or oral hypoglycemic drugs. Although the effect of standard biomedical therapy is remarkable, its long-term use is prone to toxic side effects. Numerous studies have recently found that Traditional Chinese Medicine (TCM) has strong advantages in the prevention and treatment of DM and cardiovascular complications (DACC). The collection, processing, preparation and clinical use of TCM are guided by the theory of TCM and follow the “holistic concept.” Multiple components, pathways, and targets form the basis for the use of TCM in treating multiple parts and organs of the body simultaneously. TCM is mainly derived from natural medicines and their processed products and has fewer side effects. TCM is clinically used as compound prescriptions, botanical drugs, and monomers. TCM, either independently or in combination with standard biomedical treatments, has shown unique therapeutic advantages. This review aimed to explore the recently reported mechanisms of action of TCM in the prevention and treatment of DACC. These findings will aid the optimization of the current therapy or formation of a therapeutic schedule for integrated TCM and standard biomedical treatments.